Issues for renminbi internationalization: An overview - Barry Eichengreen; Masahiro Kawai (Asian Development Bank Institute (ADBI), 2014)
The growing weight of the People's Republic of China (PRC) in the world economy, measured by gross domestic product (GDP) and trade volume, has intensified debate on the potential international role of its currency - the renminbi (RMB). This paper provides an overview of RMB internationalization issues. Reviewing the current state of RMB internationalization, the paper finds that much progress has been made on RMB settlements for trade involving the PRC and on RMB-denominated bond issuance in Hong Kong, China, but that RMB internationalization is still limited due to capital account controls. The paper argues that a high degree of RMB internationalization requires significant capital account liberalization - supported by financial market liberalization including market-determined interest rates, and by effective financial regulation and supervision - which in turn would call for greater exchange rate flexibility so that the People's Bank of China (PBOC) can enjoy monetary policy autonomy. This, however, would pose a challenge for PRC authorities as hasty capital account liberalization could expose PRC financial markets to the risk of crisis. The paper also emphasizes the importance of institutional reforms - such as making the PBOC independent from political processes, improving the judicial system to implement rule of law, raising transparency and accountability of policy making, and democratizing the political regime - to make the RMB a truly international reserve currency. Finally, the paper explores the implications of RMB internationalization for the international monetary system.
Keywords: F31; F32; F33; F41; 330; renminbi; yuan; international monetary policy; currency internationalization; foreign exchange; capital account liberalization; financial market; Renminbi; Internationaler Finanzmarkt